2022
DOI: 10.21203/rs.3.rs-1437498/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Experiences of and recommendations on clinical trial design in Alzheimer’s disease from the participant’s point of view

Abstract: Introduction. In the context of the development of pharmaceutical interventions, expectations and experiences of participants are essential. Their insights may be particularly helpful to address the challenges of recruiting and retaining participants for Alzheimer’s disease (AD) clinical trials. We examined clinical trial participants’ experiences to optimize trial design in Alzheimer’s disease (AD). Method. In this mixed-methods study, we included adults who participated in sponsor-initiated AD trials at B… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
(47 reference statements)
0
1
0
Order By: Relevance
“…Previous authors have suggested one of the reasons RCTs in AD have been largely unsuccessful is because of poor trial design. 28 There has been substantial work on methods to improve RCT design including research on participants' priorities to increase willingness to participate in RCTs, 29 suggestions to use Bayesian adaptive RCT designs, 30 and using polygenic hazard scores to stratify participants. 31 However, limited consideration has been given to the age of participants when they enter into an RCT and the accepted convention is to enroll partic-ipants over 50, 60, or 65 years to 85 years old depending on the target population, study aims or choice of outcome measure.…”
Section: Discussionmentioning
confidence: 99%
“…Previous authors have suggested one of the reasons RCTs in AD have been largely unsuccessful is because of poor trial design. 28 There has been substantial work on methods to improve RCT design including research on participants' priorities to increase willingness to participate in RCTs, 29 suggestions to use Bayesian adaptive RCT designs, 30 and using polygenic hazard scores to stratify participants. 31 However, limited consideration has been given to the age of participants when they enter into an RCT and the accepted convention is to enroll partic-ipants over 50, 60, or 65 years to 85 years old depending on the target population, study aims or choice of outcome measure.…”
Section: Discussionmentioning
confidence: 99%